Early Phonological Neural Specialization Predicts Later Growth in Word Reading Skills - Yamasaki, Brianna L.; McGregor, Karla K.; Booth, James R. (Frontiers in Human Neuroscience, 2021)
According to the Interactive Specialization Theory, cognitive skill development is facilitated by a process of neural specialization. In line with this theory, the current study investigated whether neural specialization for phonological and semantic processing at 5-to-6 years old was predictive of growth in word reading skills two years later. Specifically, four regression models were estimated in which reading growth was predicted from: (1) an intercept-only model, (2) measures of semantic and phonological neural specialization, (3) performance on semantic and phonological behavioral tasks, or (4) a combination of neural specialization and behavioral performance. Results from the preregistered analyses revealed little evidence in favor of the hypothesis that early semantic and phonological skills are predictive of growth in reading. However, results from the exploratory analyses, which included a larger sample, added age at Time 1 as a covariate, and investigated relative growth in reading, demonstrated decisive evidence that variability in phonological processing is predictive of reading growth. The best fitting model included both measures of specialization within the posterior superior temporal gyrus and behavioral performance. This work provides important evidence in favor of the Interactive Specialization Theory and, more specifically, for the role of phonological neural specialization in the development of early word reading skills.